Metal organic frameworks constructed heterojunction with α-NiS-β-NiS/CdS: The effect of organic-ligand in UiO-66 for charge transfer of photocatalytic hydrogen evolution. (May 2021) - Zhang, Heqing; Yu, Zebin; Jiang, Ronghua; Hou, Yanping; Huang, Jun; Zhu, Hongxiang; Yang, Fei; Li, Mingjie; Li, Fengyuan; Ran, Qi
Abstract: Developing favorable charge transfer mode for photocatalytic hydrogen evolution in a photocatalyst is a promising way to enhance photocatalytic activity. In this study, MOF, decorated with different functional groups, was initially used as charge transfer mode convertor coupled with CdS/α-NiS-β-NiS. The NH2 -UiO-66/CdS/α-NiS-β-NiS lead to twice and triple higher H2 evolution compared to (OH)2 -UiO-66/CdS/α-NiS-β-NiS and UiO-66/CdS/α-NiS-β-NiS respectively under simulated sunlight. The NH2 -UiO-66 provides suitable energy band structure to formed Z-scheme with CdS/α-NiS-β-NiS, which plays a synergistic role in the photocatalytic process. The loading of α-NiS-β-NiS significantly improves the visible light absorption ability and provides abundant active sites. As a result, the α-NiS-β-NiS/CdS/NH2 -UiO-66 show considerable photocatalytic hydrogen production rate of 17.88 mmol h −1  g −1, which is 7.9 times and 2.5 times as high as-those of pure CdS and 7-α-NiS-β-NiS/CdS, and it also shows a prominent apparent quantum efficiency (AQE) of 14.7% at 420 nm. This work provides a new insight design a metal organic frameworks based heterojunction with highly-efficient photo-induced charge separation and excellent visible-light absorption ability. Highlights: UiO-66 with different organic-ligands could influence charge transfer mode of photocatalyst. α-NiS-β-NiS can improve light absorption ability and provide abundant active-sites. α-NiS-β-NiS/CdS/MOF were successfully developed by a simple three-step hydrothermal method.